Genome-wide identification and characterization of pectin methylesterase inhibitor gene family members related to abiotic stresses in watermelon - Zhang, Siyu; Yuan, Xinhao; Duan, Jiahao; Hu, Jun; Wei, Chunhua; Zhang, Yong; Wang, Jiafa; Li, Chao; Hou, Shengcan; Luo, Xiaodan; Li, Junhua; Zhang, Xian; et al. (Frontiers in Plant Science, 2024)
Pectin is a vital component of plant cell walls and its methylation process is regulated by pectin methylesterase inhibitors (PMEIs). PMEIs regulate the structural and functional modifications of cell walls in plants and play an important role in plant processes such as seed germination, fruit ripening, and stress response. Although the PMEI gene family has been well characterized in model plants, the understanding of its molecular evolution and biological functions in watermelon remains limited. In this study, 60 ClPMEI genes were identified and characterized, revealing their dispersion on multiple chromosomes. Based on a systematic developmental analysis, these genes were classified into three subfamilies, which was further supported by the exon, intron, and conserved motif distribution. Analysis of cis-elements and expression patterns indicated that ClPMEIs might be involved in regulating the tolerance of watermelon to various abiotic stresses. Moreover, distinct ClPMEI genes exhibit specific functions under different abiotic stresses. For example, ClPMEI51 and ClPMEI54 showed a significant upregulation in expression levels during the late stage of drought treatments, whereas ClPMEI3 and ClPMEI12 displayed a significant downregulation under low-temperature induction. Subcellular localization prediction and analysis revealed that the ClPMEI family member proteins were localized to the cell membrane. This study provided an important foundation for the further exploration of the functions of ClPMEI genes in watermelon.